IEDB‐3D 2.0: Structural data analysis within the Immune Epitope Database. (17th March 2023) - Mendes, Marcus; Mahita, Jarjapu; Blazeska, Nina; Greenbaum, Jason; Ha, Brendan; Wheeler, Kelly; Wang, Jiyao; Shackelford, Deborah; Sette, Alessandro; Peters, Bjoern
Abstract: The Immune Epitope Database (IEDB) catalogs T cell, B cell, and major histocompatibility complex ligand information in the context of infectious disease, allergy, autoimmunity, and transplantation. An important component of this information is three‐dimensional structural data on T cell receptors, antibodies, and pairwise residue interactions between immune receptors and antigens, which we refer to as IEDB‐3D. Such data is highly valuable for mechanically understanding receptor:ligand interactions. Here, we present IEDB‐3D 2.0, which comprises a complete overhaul of how we obtain and present 3D structural data. A new 3D viewer experience that utilizes iCn3D has been implemented to replace outdated java‐based technology. In addition, we have designed a new epitope mapping system that matches each epitope available in the IEDB with its antigen structural data. Finally, immunogenicity data retrieved from the IEDB's ImmunomeBrowser can now be used to highlight immunogenic regions of an antigen directly in iCn3D. Overall, the IEDB‐3D 2.0 provides an updated tool platform to visualize epitope data cataloged in the IEDB.